Block starts and acceleration mechanics - Tellez, T. (2008)
A 5 minute teaser from HPC ELITETRACK Gold Medal Clinic DVD. This particular lecture is by legendary sprint coach Tom Tellez. Tom is the former coach of sprint greats Carl Lewis, Mike Marsh, and Leroy Burrell. Tom speaks about block settings, acceleration mechanics and other important aspects of the start. This lecture was filmed at the 2008 Olympic Trials Super Clinic.